Kitab Tibb dan Usada: Perbandingan Gangguan Mental Pada Tradisi Melayu dan Bali - Afandi, Haekal Rheza (Perpustakaan Nasional Republik Indonesia, 2025)
This study investigates the treatment of mental disorders recorded in traditional manuscripts, specifically the Kitab Tibb and Usada from Malay and Balinese traditions. The research reveals that the Kitab Tibb details eight types of mental disorders, while the Usada categorizes ten, including eating disorders, anxiety disorders, and PTSD (Post-Traumatic Stress Disorder). The comparative literature method is employed to analyze the symptoms of these disorders as documented in both texts. One of the key aspects highlighted in the study is the importance of understanding the cultural and historical context surrounding mental health treatment. The social and political changes occurring in the 15th and 16th centuries had a significant influence on how communities perceived and addressed mental health issues. By documenting the medicinal knowledge available in the Kitab Tibb and Usada, the study suggests that traditional medicine can serve as a valuable alternative for individuals who may not find modern approaches suitable. This research opens up opportunities for the integration of traditional and contemporary medical practices, aiming to create more comprehensive solutions for treating mental disorders. Ultimately, it seeks to enrich the mental health field by promoting alternative approaches and encouraging further research into the effectiveness of traditional remedies.